Forecasting of Carbon Monoxide Concentration Based on Sequence-to-Sequence Deep Learning Approach - Zaini N.; Ean L.W.; Ahmed A.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Air quality; Brain; Carbon monoxide; Errors; Forecasting; Mean square error; Network architecture; Air pollutants; Carbon monoxide concentration; Convolutional neural network; Deep learning; Forecasting models; Human health; Learning approach; Monitoring stations; Root mean square errors; Sequence models; Long short-term memory